Organogelators based on iodo 1,2,3-triazole functionalized with coumarin: properties and gelator-solvent interaction - Huang, Yaodong; Zhang, Yan; Yuan, Yuqin; Cao, Wenwen (Tetrahedron, 2015)
A new family of 1,2,3-triazole derivatives containing coumarin functional group with different alkyl chain lengths was synthesized and their gelation abilities and photochemistry properties were fully characterized. The main force for the self-assembly in gel state are π-π stacking and van der Waals interaction. Solubility parameters and Teas plots of the gelator and several single solvents were calculated to estimate the gelator-solvent interaction. The organogel in a binary solvent system was also characterized using various microscopic techniques including X-ray diffraction (XRD), scanning electron microscopy (SEM) and UV–vis. Reversible and stereoselective [2+2] cyclo-addition of the gel was confirmed by 1H NMR, UV absorption, fluorescence spectra and SEM. The gels formed were affected and destroyed by the addition of mercury ion. [Display omitted]